2001
DOI: 10.1093/aje/153.8.783
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight, Childhood Growth, and Cardiovascular Disease Risk Factors in Japanese Aged 20 Years

Abstract: To determine whether birth weight and childhood growth, especially rate of height increase, are independently related to major cardiovascular disease risk factors in adult life, the authors conducted a 20-year follow-up study in a Japanese population, using the record-linkage method. From medical checkup data for babies and for residents aged 20 years in Ishikawa, Japan, the authors obtained 20-year follow-up data (1985-1994) on 4,626 participants (2,198 men and 2,428 women) born in 1965-1974. Using multiple l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
66
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 36 publications
8
66
0
Order By: Relevance
“…11,14,45,52 Although some studies of adults found significant relationships when men and women were analyzed together, 10 when males and females were analyzed separately in these same studies significant relationships were only seen in men. 13,42,54 These agree with our findings of a possible sex difference in effect in total cholesterol, and studies that have analyzed men and women together may have obscured a relationship in men. However, evidence in our study for a sex difference was relatively weak and may represent a chance finding, while the small size of the effect, even among the men, means that it is likely to be of limited public health importance.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…11,14,45,52 Although some studies of adults found significant relationships when men and women were analyzed together, 10 when males and females were analyzed separately in these same studies significant relationships were only seen in men. 13,42,54 These agree with our findings of a possible sex difference in effect in total cholesterol, and studies that have analyzed men and women together may have obscured a relationship in men. However, evidence in our study for a sex difference was relatively weak and may represent a chance finding, while the small size of the effect, even among the men, means that it is likely to be of limited public health importance.…”
Section: Discussionsupporting
confidence: 88%
“…41 The detrimental impact of greater gain in weight relative to height during the life-course is also implicated in the findings for HDL, with the strengthening of the positive association after adjustment for current BMI. 18 Relationships between total cholesterol and birth weight have previously been found in subjects with nonfasting 13,42 and fasting lipid levels, 43,44 whereas significant relationships with other lipids were generally only seen in studies using fasting lipid levels. 11,[45][46][47] The use of nonfasting measures in the NSHD may explain our lack of association of birth weight with LDL and HDL cholesterol.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies do not directly compare effects of growth in height versus weight. For example, Miura et al 20 reported an inverse relation of rate of height gain from age 3 to 20 years on systolic BP in Japanese young adults. Law et al 17 reported effects of weight gain but did not show results for height.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews have reported inverse associations between birth weight and blood pressure (Huxley et al 2000), serum glucose level (Whincup et al 2008), total cholesterol concentration (Owen et al 2003) and metabolic syndrome (Silveira and Horta 2008). Miura et al (2001) reported inverse associations between birth weight and blood pressure and serum cholesterol in a Japanese cohort population.…”
mentioning
confidence: 96%